An American Sign Language Translation Website for Fourth Grade Elementary Science Terminology (TARI) - Ida Ayu Mayun Wulantari; Riastini Putu Nanci; Utami Ketut Herya (Universitas Pendidikan Ganesha, 2026)
Science learning for deaf students in inclusive elementary schools continues to face significant challenges, particularly in understanding scientific terminology that is abstract and dominated by English loanwords. The limited availability of science terminology equivalents in Indonesian Sign Language systems restricts deaf students’ access to scientific knowledge. This study aimed to develop and evaluate an American Sign Language (ASL) translation website for fourth-grade elementary school science terminology, entitled the Terminology ASL Resource Initiative (TARI). The research employed a Research and Development approach using the ADDIE model, implemented up to the development stage. Participants included science content experts, digital learning media experts, teachers, and students. Data were collected through user readiness checklists based on the Technology Readiness Index (TRI) 2.0, expert validation instruments, and user response questionnaires. The results indicate that user readiness was categorized as very high, content validity achieved a very high level, and the website demonstrated excellent practicality according to both teachers and students. These findings suggest that the TARI website is a valid and practical digital learning resource that supports inclusive science education by improving accessibility and facilitating the understanding of scientific terminology for deaf students at the elementary school level.